Sistem Pendukung Keputusan Pemilihan Karir Mahasiswa Informatika dengan Metode SAW - Arya Agus Wicaksana; A Sidiq Purnomo (Lembaga Pengembangan Kinerja Dosen, 2025)
The significant mismatch between graduates’ competencies and industry demands poses a critical challenge in career decision-making, particularly within the field of Information Technology.